Development of students’ teaching and research skills in the process of applying mathematical software for calculating integrals that depend on the parameter - Бугаєць, Н. О. (Pedagogy of Higher and Secondary Education, 2021)
Basic possibilities of the use of programmatic facilities of the mathematical setting are examined for uniting of tasks on the calculation of integrals, dependebcy upon a parameter. Attention applies on a question of development educational-research abilities of students.